Keefektifan Em-4 (Effective Microorganism-4) Dalam Menurunkan Chemical Oxygen Demand (Cod) Limbah Cair Industri Batik - Ramlan, Muh; , Dwi Astuti, M. Kes (2017)
Based on the results of examination of COD in industrial waste water Nggemblegan Village sub district Kalikotes batik Klaten exceeds standard quality raw wastewater Perda Jateng No. 5 in 2012 that is 482.5 mg/l. purpose of this research is to analyse the effectiveness of EM-4 in lowering levels of COD of waste liquid batik industry. Experimental method used with pretest-posttest design with control group. The number of samples used is 12 litres, each treatment takes 1 liter of waste with 3 repetitions. The results of the laboratory test on the levels of COD, controls an average of 447.3 mg/l, and in the treatment group 1 ml/l, 2 l, and ml/3 ml/l COD levels an average of 393.2 mg/l, 302.6/l, mg 280.2 mg/l. dose effect on the decline of COD in the dose of 3 ml/l of 72,5%. The results of the anova statistical test shows (p < 0.01) there is the influence of the EM-4 against a decline in the levels of COD of waste batik.